The implications of poor sleep quality on arterial health in persons with multiple sclerosis - Brooke M. Shafer; Sushant M. Ranadive; Tracy Baynard; Robert W. Motl; Bo Fernhall (Artery Research, 2017)
Background: Multiple sclerosis (MS) is associated with increased risk of cardiovascular disease (CVD) and approximately 25–54% of patients report poor sleep quality. There is evidence from the general population of an association between poor sleep and increased CVD risk, but this is poorly understood in MS. Purpose: This study examined the association between self-reported sleep quality and arterial health in persons with MS. Methods: MS subjects (n = 31) and control subjects (n = 23) were recruited. Control subjects were age and body size matched. All subjects were administered the Pittsburgh Sleep Quality Index (PSQI) to assess self-reported sleep quality. Subjects with a global score >5 were classified as “poor sleepers”. Blood pressure, arterial stiffness, and the forearm blood flow responses following 5-min ischemic occlusion (endothelial function) were measured. Results: Nineteen MS subjects and 5 control subjects were classified as “poor sleepers”. AIx was significantly higher in MS subjects who had poor sleep quality (32.5 ± 8.8 vs 22.0 ± 13.2; P < 0.05). Conclusions: Markers of arterial dysfunction were significantly higher in MS subjects with poor sleep quality compared to those with good sleep quality. This study suggests novel evidence for the association of CVD risk and sleep quality in MS.